Controversias constitucionales en la interpretación de la base imponible del impuesto por distribución de utilidades de sucursales en el país de entidades no domiciliadas - Zevallos Miranda, Osman Francisco (2021)
This research work approaches the constitutional controversy generated by the interpretations of SUNAT and the Tax Court of the Second Paragraph of Subparagraph e) of the Article 56 of the Income Tax Law that regulates the tax basis of the tax for the dividend’s distribution from branches in Peru to no-domiciled head office. Both SUNAT and the Tax Court consider that in order to establish the taxable base of the tax, the Income Tax Law provides a fiction that does not allow to consider the losses of previous years, which generates in some cases that the non-domiciled entity must pay tax on a profit distribution that does not exist because it still has losses from previous years. We consider that the interpretation of SUNAT and the Tax Court vulnerates constitutional principles that assist the non-domiciled taxpayer, such as the Constitutional Principles of respect for Tax Capacity, Reserve of Law, Non-Confiscation and Equality in tax matters. We believe that within the Income Tax Law it is possible to find an interpretation that respects the constitutional limits imposed by the Political Constitution of Peru. Thus, under the interpretation methods of historical, literal, systematic interpretation due to the location of the norm and interpretation in accordance with the constitution, we believe that it is possible to consider losses to determine the tax basis in the determination of Income Tax for branch profits distribution to non-domiciled entities. Additionally, in the development of this research work we reviewed the tax treatment that has been given to the tax on the distribution of profits by branches in Colombia, Mexico and Chile, concluding that in all of them it has not been forbidden to consider losses from previous years to determinate the basis of the tax.